2008
DOI: 10.4161/cc.7.23.6993
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mutations contribute to cell motility and invasion by affecting its main regulators

Abstract: (2008) BRCA1 mutations contribute to cell motility and invasion by affecting its main regulators, Cell Cycle, 7:23, 3781-3783,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…17,18 Inversely, loss of BRCA1 resulted in an increase in cell proliferation and a transition of cell cycle, 29,30 and contributed to breast cancer cell migration by affecting its main regulators, such as caveolin-1. 31,32 Our data in the present study revealed that the above-mentioned effects of EZH2 downregulation require the expression of BRCA1, as inhibition of BRCA1 partly rescued the decrease in cell proliferation, migration, and the delay in G 2 /M transition caused by EZH2 depletion. Consistently, preceding studies reported that EZH2 could modulate BRCA1-mediated cell proliferation in breast cancer.…”
Section: Discussionsupporting
confidence: 57%
“…17,18 Inversely, loss of BRCA1 resulted in an increase in cell proliferation and a transition of cell cycle, 29,30 and contributed to breast cancer cell migration by affecting its main regulators, such as caveolin-1. 31,32 Our data in the present study revealed that the above-mentioned effects of EZH2 downregulation require the expression of BRCA1, as inhibition of BRCA1 partly rescued the decrease in cell proliferation, migration, and the delay in G 2 /M transition caused by EZH2 depletion. Consistently, preceding studies reported that EZH2 could modulate BRCA1-mediated cell proliferation in breast cancer.…”
Section: Discussionsupporting
confidence: 57%
“…Decreased BRCA1 expression in human sporadic breast cancer tissues is linked to the expression of cell cycle regulatory proteins 61. Yasmeen and colleagues have recently demonstrated for the first time that the BRCA1‐mutation deregulates the expression patterns of P‐cadherin, Caveolin‐1 as well as E‐cadherin 62. Furthermore, they also revealed that BRCA1 downregulates Id‐1 expression in human mammary epithelial cells 62.…”
Section: Discussionmentioning
confidence: 99%
“…1). More contritely, restoration of BRCA1 and BRCA2 expression in these cell lines did not affect the ability of VSV to replicate in these cells; whereas the stable transfection of full length BRCA1 and BRCA2 cDNA restores cell cycle progression and blocks cell motility and invasion induced by these specific mutations in human primary breast and ovarian cells 7 ; and unpublished data in contrast, the control cells of human normal mammary epithelial cells expressing E6/E7 onco-proteins of HPV type 16 were killed by the VSV. In conclusion, our study shows clearly that VSV instillation therapy is questioned since the selective ability of this virus to kill cancer cells while sparing the normal cells is not confirmed, based on our study of matched normal and cancer cell lines established from the same patients; which suggests that VSV could replicate in normal as well as cancer cells in the majority of the cases.…”
Section: Dear Editormentioning
confidence: 79%